Perceptions of pain relief after surgery. Issue 6741 (30th June 1990) - Kuhn, S; Cooke, K; Collins, M; Jones, J M; Mucklow, J C
Abstract : OBJECTIVE–To assess patients' satisfaction with postoperative pain relief. DESIGN–A descriptive and questionnaire study of patients' experience. SETTING–Two surgical and two gynaecological wards. PATIENTS–50 Patients admitted to hospital for cholecystectomy and 51 admitted for hysterectomy. MAIN OUTCOME MEASURES–Visual analogue scales with no divisions were completed by the patients immediately after each dose of postoperative analgesia was administered throughout their stay in hospital. A questionnaire completed on the fifth postoperative day recorded patients' recollections of their experience. Opinions were also sought from medical and nursing staff. RESULTS–During the first 24 hours after surgery recorded pain levels were 60% of the maximum and were not influenced by age, sex, or the type of operation performed. The median interval between the return of pain and a further injection of analgesic was 2 hours (interquartile range 1 to 3.5 hours). Expectations of pain relief were low, and for 70% of the patients the pain was at least as bad as they had expected. Only half of the medical and nursing staff questioned thought that postoperative analgesia should relieve pain completely; drugs were prescribed and administered with too little attention to the patient's response and too much concern about adverse effects and opioid dependence. CONCLUSIONS–The results suggest that the standard of postoperative pain relief is poor because of inadequate education of patients in what to expect (and demand), and of medical and nursing staff in how to prescribe and administer analgesia with reference to individual drug response.